Does city Structure affect the labor market outcomes of black workers? - Harris Selod; Yves Zenou (Institute for the Study of Labor (IZA), 2003)
In this paper, location choices are driven by households (both blacks and whites) consciously choosing to trade off proximity to neighbors of similar racial backgrounds for proximity to jobs. Because of coordination failures in the location choices, multiple urban equilibria emerge. There is a ?Spatial-Mismatch Equilibrium? in which blacks reside far away from jobs and experience high unemployment rates and a ?Spatial-Matching Equilibrium? in which blacks are closer to jobs and experience lower unemployment rates. Under some reasonable condition, we demonstrate that all workers are better off under the Spatial-Matching Equilibrium, leaving a role for policy intervention.
Keywords: R14; J15; 330; spatial mismatch; multiple equilibria; racial preferences; social networks; labor discrimination; Wohnstandort; Arbeitsplatz; Städtischer Arbeitsmarkt; Städtische Arbeitslosigkeit; Schwarze; Soziales Netzwerk; Standorttheorie; Theorie